SWK-08. DELAYED DIAGNOSIS OF CENTRAL NERVOUS SYSTEM (CNS) TUMORS IN CHILDREN: PERSPECTIVE FROM THE FRONTLINE - Jogendran, Manisha (Neuro Oncol, 2020)
Delayed diagnosis of CNS tumors in children is well documented, partially due to challenges in recognizing rare diagnoses. Our objective was to describe Canadian family physicians’ attitudes and confidence in diagnosing and managing pediatric CNS tumors. A standardized questionnaire was administered at a Canadian national family physicians’ conference. Items were based on observations from our institutional study of prediagnostic symptomatic interval in pediatric CNS tumors. 449 surveys were completed. 302/443 (68%) physicians practice in cities. 153/447 (34%) report encountering parents that inquire about their children having brain tumors. 261/449 (58%) have not managed a pediatric brain tumor. 153/447 (34%) report they are not confident, 255/447 (57%) somewhat confident and 39/447 (9%) confident in managing a suspected brain tumor in a stable child. 259/447 (58%) would refer directly to a hospital/specialist. The reported median time for suspicion of a brain tumor was 8–14 days for children with vomiting and/or headache and 1 day for children with seizure and/or ataxia. 410/447 (97%) report not knowing any guidelines to help with management. 235/447 (53%) suggested barriers they experience to include 52/235 (22%) wait times for imaging/specialists, 37/235 (16%) geographical location of the child, 27/235 (12%) knowledge, 25/235 (11%) access to imaging/specialist, and 15/235 (6%) patient-related factors or system barriers, and 8/235 (3%) specialist attitudes. 68/235 (29%) identified no barriers in their practice. This study provides insight into family physicians’ perceived challenges and barriers in diagnosing and managing new suspected pediatric CNS tumors. Educational effort and overcoming systemic perceived barriers may increase physicians’ confidence.